Investigations on Dielectric Resonator Antennas for Ultra-Wide Band Applications - Yadav, Sachin Kumar (My University, 2022)
As the recent trending wireless systems are trending upward, UWB technology heralds a new age for wireless communication systems. It has a high data rate while consuming low power. Communication is becoming a part of the everyday living of individuals. As such, to accomplish efficient and proper wireless communication, compact and effective radiators are required. Undoubtedly, one of the effective radiators is a dielectric resonator antenna (DRA). The DRA is economical and has attractive highlights such as simple planning, basic construction strategies, and adaptability in the structure to meet the required frequencies. DRAs are superior and preferred replacements with printed antennas and microstrip patch antennas due to their high radiation efficiency, high data transfer capability, and adaptability of polarization. This thesis recommends wide bandwidth and wide axial ratio bandwidth in a rectangular DRA (RDRA). With miniaturized DRA, some techniques such as air-spaced within dielectric resonator structure, perturbation theory, defective ground structure, stacking, segmenting, and merging modes of bandwidth improvement achieve the ultra-wideband operations. It also includes UWB DRA with multiple-input multiple-output (MIMO) configuration. In objective 2, an air-spaced DRA is designed, simulated, and fabricated for UWB operations. This antenna consists of a rectangular dielectric resonator, microstrip feedline, and modified ground plane. A cylindrical-shaped structure is extracted from a solid rectangular DR to improve the antenna's gain and impedance bandwidth. The present work demonstrates gain enhancement by increasing the diameter of the air-gap within the solid structure of the RDR. A defective ground structure (DGS) is used to improve the antenna's impedance bandwidth in order to achieve UWB operation. The proposed antenna has a 104.09% impedance bandwidth (3.28 to 10.4 GHz) with a peak gain of 7.2 dB at 7.8 GHz. OM-shaped DRA and Stacked Asymmetric DRA are two designs presented by Objective 3. First design, dielectric resonator (DR) modified to an ‘OM’ shape for UWB (3.1 to 11.3GHz) operations to support high data rate multimedia applications for 4G/5G communications. It has overall antenna dimensions of 50 × 40 × 4.87 mm3. DRA is excited by a P-type transformer fed that offers an input impedance of 50 Ω. A conformal strip is attached between the feedline and the OM-shaped DR to improve DRA impedance matching. This ‘OM’ shaped DR structure excites the TE111 mode at 4.9 GHz, and two higher-order modes as TE211, and TE221, at 7.2 and 8.35 GHz, respectively. The proposed DRA has an impedance bandwidth of 8.2 GHz from 3.1 to 11.3 GHz with a peak gain of 7.68 dB at 10.5 GHz. the proposed DRA exhibits an elliptically polarized behavior with axial ratio bandwidth of 5.1GHz (≤ 10dB) from 6 to 11.1 GHz. A compact circularly polarised asymmetric-stacked DRA for UWB operations is developed in the second design, which is excited by a transformer-type feedline. The proposed DRA consists of two rectangular ceramic blocks with the same permittivity (DR = 9.8) but differing in height and width of DR, and an F-shaped metal strip added to the partial ground, which achieves the widen axial ratio bandwidth. The proposed antenna is supported fundamental and third-order modes as TE_δ11 and TE_δ13 at 9.1 and 11.28 GHz, respectively. The proposed antenna covers 6.4 to 12.4 GHz (impedance bandwidth of 63.8 %) with a peak gain of 6.01 dBi at 11.5 GHz and AR bandwidth (≤ 3 dB) is reported 63.8% (6.4 to 12.4 GHz. Objective 4 has proposed two MIMO DRA designs as rack-shaped DRA and cross-strip based DRA. In the first design, a rack-shaped two radiator element MIMO DRA is proposed for ultra-wideband applications. Two rectangular-shaped radiator elements are used to implement the proposed MIMO antenna structure, which are further transformed into rack-shaped dielectric resonators (DRs). An inverted T-shaped metallic strip is placed between two radiators to achieve the impedance bandwidth of 101.87 % (3.54 to 10.89 GHz) with isolation of 15.6 dB. Second design has better impedance bandwidth and isolation as compare to design 1. The cross-metallic strip based RDRA consists of two RDR, Inverted T- shaped metallic strip, scissor-shaped defected ground structure, cross-shaped metallic parasitic strips, and ground stub. Which provides an impedance bandwidth of 104.6 %, covering frequency from 3.3 to 10.8 GHz with isolation of 20 dB. The MIMO diversity parameters are implemented within the limit in both proposed design.
Ph.D. thesis
Keywords: DRA; UWB; Circularly Polarized Antennas; MIMO; QWT transformer